2013
DOI: 10.1155/2013/347312
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Methyl-4-Phenylpyridinium Ion, Rotenone, and Paraquat on Differentiated SH-SY5Y Cells

Abstract: Paraquat (PQ), a cationic nonselective bipyridyl herbicide, has been used as neurotoxicant to modulate Parkinson's disease in laboratory settings. Other compounds like rotenone (ROT), a pesticide, and 1-methyl-4-phenylpyridinium ion (MPP+) have been widely used as neurotoxicants. We compared the toxicity of these three neurotoxicants using differentiated dopaminergic SH-SY5Y human cells, aiming to elucidate their differential effects. PQ-induced neurotoxicity was shown to be concentration and time dependent, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Many recent studies have shown that exogenous environmental toxins, such as PQ are linked to PD (Tufekci et al, 2011 ; Baltazar et al, 2014 ). Here, we show that PQ is significantly toxic to SH-SY5Y cells in a time and dose dependent manner which is consistent with a recent study (Martins et al, 2013 ). PQ exposure leads to neuronal cell death in vitro and in vivo; though exact mechanisms of selective neurodegeneration induced by PQ in dopaminergic neurons are still unknown (Berry et al, 2010 ).…”
Section: Discussionsupporting
confidence: 94%
“…Many recent studies have shown that exogenous environmental toxins, such as PQ are linked to PD (Tufekci et al, 2011 ; Baltazar et al, 2014 ). Here, we show that PQ is significantly toxic to SH-SY5Y cells in a time and dose dependent manner which is consistent with a recent study (Martins et al, 2013 ). PQ exposure leads to neuronal cell death in vitro and in vivo; though exact mechanisms of selective neurodegeneration induced by PQ in dopaminergic neurons are still unknown (Berry et al, 2010 ).…”
Section: Discussionsupporting
confidence: 94%
“…MPP + did not induce extracellular LDH suggesting the absence of plasma membrane damage (Martins et al . ), while Mn elevated extracellular LDH (Fig. d).…”
Section: Discussionmentioning
confidence: 84%
“…A previous study showed that significant cell death of RA-differentiated cells was observed after 24 hours of exposure to 500 and 1000 μ M MPP + , and there was no apparent increase in the cell death by extending the exposure period to 48 hours [ 22 ]. For undifferentiated cells, studies showed that cell viability decreased to approximately 50% when cells were treated with 500 μ M MPP + for 24 hours [ 7 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%